Kościoły i parafie diecezji ełckiej (cz. 16) - Guzewicz, Wojciech (Civitas et Lex, 2024)
The article presents the church centers in Olecko (Holy Family), Olecko – Lesk (Assumption of the Blessed Virgin Mary), Olszewo Węgorzewskie (Exaltation of the Holy Cross), Orłowo (Saint Kazimierz) and Orzysz (Our Lady of the Scapular).